Pharmaceutical care in Alzheimer's Disease (Research, Society and Development, 2021)
Alzheimer's Disease (AD) is a neurodegenerative disorder and the main cause of dementia, as the disease initially affects the hippocampus and slowly progresses to other parts of the brain, causing cell damage and death, specifically of neurons, generating irreversible damage and consequences for all cognitive functioning. , affective, intellectual and behavioral, negatively influencing the individual's autonomy and independence. Patients are undergoing treatments for chronic use, as there is no cure for Alzheimer's disease. Treatment aims to minimize the symptoms of the disease, enabling partial improvement to prolong survival and delay progression. Given the real importance of pharmaceutical assistance directed to the patient, which optimizes the response of a given pharmacotherapy, through which the pharmacist, together with the patient, carries out a follow-up plan. In this context, this work aims to highlight the importance of pharmaceutical care both in pharmacotherapy and outside it. This is a cross-sectional and descriptive integrative review study with a qualitative and quantitative approach on the subject, where searches were made in the Scielo and VHL databases about the subject. A total of 1,199 works were found, in which a screening was carried out to collect the results. It was observed that the treatment of Alzheimer's Disease is capable of delaying or temporarily stagnating the advance of symptoms, aiming to alleviate cognitive deficits, behavioral changes and improve the quality of life of the patient and his family. The treatment of Alzheimer's Disease must be multidisciplinary and with the objective of providing stabilization of cognitive impairment, modifying the manifestations of the disease, with a minimum of adverse effects. In this context, immunomodulators are more likely to become drugs capable of influencing the course of AD, as the selected studies had better quality and the results were promising. On the other hand, the toxicity of drugs for the treatment of AD is a major obstacle, and to overcome this situation, the presence of pharmaceutical care becomes increasingly essential.